Stoichiometry of animal manure and implications for nutrient cycling and agriculture in sub-Saharan Africa - Sileshi, Gudeta W.; Nhamo, N.; Mafongoya, P.L.; Tanimu, J. (Springer, 2017)
A number of studies have recommended application of large quantities of manure alone or in combination with inorganic fertilizer in sub-Saharan Africa (SSA). However, yield responses of cereals such as maize are very modest even at manure application rates exceeding 10 t ha−1 year−1. We conducted a meta-analysis of data from 64 studies across 14 countries in SSA in order to explore variability in nutrient concentrations, stoichiometry and maize yield responses to animal manure. We observed novel instances of stoichiometry and correlations between organic carbon (C), total nitrogen (N), phosphorus (P) and potassium (K) concentrations, and elemental ratios in manure. In 27% of the manure samples the C:N ratio was greater than 25 indicating that N will be potentially unavailable to crops due to net immobilization. In over 94% of the manure samples, the N:P and C:P ratios were <15 and <200 indicating net P mineralization. Therefore, decomposition rates and crop responses are likely to be N-limited rather than P-limited in the majority of the manure applied. Our analyses also demonstrate that manure application rates and N and P concentrations are less important than C:N and N:P ratios in determining maize yield response to manure. Therefore, emphasis in the future should not be on increasing manure application rates but on approaches that ensure favourable C:N and N:P ratios. Our findings also suggest the need for feeding animals with high quality diet to get better quality manure, higher crop yields and improve household food security in SSA.